Modification of expanded graphite and its adsorption for hydrated salt to prepare composite PCMs. (25th March 2018) - Zhou, Siyu; Zhou, Yan; Ling, Ziye; Zhang, Zhengguo; Fang, Xiaoming
Highlights: An expanded graphite (EG) based composite containing MgCl2 ·6H2 O is obtained. The modification of EG increases its adsorptive capacity for MgCl2 ·6H2 O. The composite maintains a similar melting point to that of MgCl2 ·6H2 O. Supercooling is reduced from 11.2 °C for MgCl2 ·6H2 O to 1.3 °C for the composite. The MgCl2 ·6H2 O/EG composite block exhibits good thermal reliability. Abstract: MgCl2 ·6H2 O is a promising inorganic phase change material (PCM) with abundant resources from salt lakes, while its wide applications are greatly hampered by the drawbacks of phase separation, supercooling and corrosivity, inherent in hydrated salts. Herein a novel expanded graphite (EG) based composite PCM containing MgCl2 ·6H2 O was explored, which involved modifying EG for increasing its hydrophilicity, compressing the modified EG (MEG) into round blocks, and immersing the blocks into melted MgCl2 ·6H2 O. The optimal mass ratio of TX-100 to EG and the favorable packing density of the MEG block are determined to be around 0.06 and 350 kg/m 3, at which the adsorptive capacity of the modified EG block reaches 80% for MgCl2 ·6H2 O, larger than 73% of the unmodified one. The as-prepared MgCl2 ·6H2 O/MEG composite block, which consists of 80.1% of MgCl2 ·6H2 O, 1.1% of TX-100, and 18.8% of EG, maintains a similar melting point to that of MgCl2 ·6H2 O, and its latent heat is as high as 116.7 J/g. Furthermore, the supercooling degree of the composite block is found to be around 1.3 °C, much less than 11.2 °C of MgCl2 ·6H2 O. The thermal conductivity of the composite block is about 7.7 times as large as that of MgCl2 ·6H2 O. And the composite exhibits a decrease only by 2.7% in phase change enthalpy after 500 thermal cycles, much lower than 41.7% for MgCl2 ·6H2 O. These good thermal characteristics make the MgCl2 ·6H2 O/MEG composite PCM show great potentials in practical applications.